Beyond Oil: Strategic Tax and Investment Reforms for Iran's Economic Resilience and Diversification - Jafari , Aidin; Faghihi , Erfan (Business, Marketing, and Finance Open, 2024)
This study rigorously analyses Iran's economic reliance on oil, highlighting the consequent weaknesses such as fiscal instability, constrained economic productivity, and inadequate workforce investment. Historically, oil earnings have supported Iran's budgetary policies; nevertheless, this reliance has rendered the government vulnerable to global oil market volatility, international sanctions, and a limited economic foundation. The essay presents a bifurcated solution architecture to tackle these difficulties, highlighting targeted tax reforms and smart sectoral investments as critical measures for economic diversification and resilience. Proposed key tax measures encompass progressive income tiers, corporation taxes on monopolies, value-added tax on luxury items, and a stamp fee on high-value assets. These initiatives seek to stabilise and diversify Iran's financial streams, promoting a more egalitarian fiscal framework that is less dependent on oil money. The essay supports these reforms by advocating for investment in renewable energy, technology, tourism, and car manufacturing—sectors selected for their growth potential and ability to diminish oil dependency, generate employment, and draw foreign investment. This strategy aims to shift Iran's economy towards sustainable growth by utilising public-private partnerships, foreign direct investment, and the National Development Fund of Iran. Collectively, these initiatives provide a framework for Iran to transcend its dependence on oil, fostering a diverse and robust economic model that is less susceptible to external influences and more congruent with its long-term developmental objectives.